RESPON BKsPPI TERHADAP ISU-ISU KEUMATAN KONTEMPORER - Muhammad Fauzan Adzima; Nirwan Syafrin; Muhyani Muhyani (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is based on the current era of globalization, there are many various life problems that occur. All events that continue to occur both in terms of social problems related to religion, ethnicity, and culture. The emergence of public issues including radicalism, secularism, liberalism, terrorism, and other public issues is no longer a new challenge for Muslims to answer. However, these issues continue to grow, especially in the international arena. The objectives of this study were (1) to determine the response of BKsPPI to public issues, (2) to determine the method of BKsPPI's da'wah in responding to public issues. This research method is a type of qualitative research method with a conceptual analysis approach and theoretical analysis. Data collection techniques are carried out by means of interviews, analysis and documentation. The findings of this study are the BKsPPI's response to five contemporary issues that exist in society, the next finding is the da'wah method used by BKsPPI in responding to contemporary ummah issues. Conclusion BKsPPI's response to contemporary public issues is to provide a response to straighten and provide solutions or solutions related to secularism, liberalism, pluralism, terrorism, and radicalism. The da'wah methods used by BKsPPI in responding to contemporary issues are the syamilah (comprehensive) method, the wasathiyah method, the direct method, the indirect method, the wisdom method, the method of socializing the five cultures, the method of da'wah code of ethics, the method of establishing friendship and fostering ukhuwah, the tafaqquh fiddin method, and the iqomatuddin method. Keywords: Response, BKsPPI, People, Contemporary